2013
DOI: 10.1021/jp4013202
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Synthesis of Au–Pd Alloy Nanodendrites and Their Catalytic Activity

Abstract: Au−Pd bimetallic nanocrystals with well-defined dendritic morphology, uniform size, and homogeneous alloy structure were synthesized in an aqueous solution by using ascorbic acid as the reductant and triblock copolymer P123 as the stabilizing agent. In this synthesis, ascorbic acid played a key role in directing the nanodendritic morphology while the presence of Pd was mandatory for the formation of well-defined nanodendrites. Without Pd, only faceted nanoparticles of gold were formed under the same reaction c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 67 publications
(196 reference statements)
5
73
0
Order By: Relevance
“…1D). This value is matched well with the d-spacing value of the (111) planes of PdAu alloy [24], which is also in good agreement with those taken from another particle with the d-spacing distances of 0.228 nm and 0.234 nm (Fig. 1C).…”
Section: Characterizationsupporting
confidence: 88%
See 1 more Smart Citation
“…1D). This value is matched well with the d-spacing value of the (111) planes of PdAu alloy [24], which is also in good agreement with those taken from another particle with the d-spacing distances of 0.228 nm and 0.234 nm (Fig. 1C).…”
Section: Characterizationsupporting
confidence: 88%
“…2, [26]. Notably, the diffraction peaks coincidently lie between the corresponding phase peak positions of bulk Au and Pd, thus strongly reflecting the formation of PdAu alloy [24]. indicating the presence of Au 0 and Au III [26].…”
Section: Characterizationmentioning
confidence: 77%
“…9 It has shown that the Pd is a promising electrocatalyst because of much cheaper than Pt and highly electroactive to the small organic molecules (i.e. lowmolecular weight alcohols) oxidation in alkaline media 1,3,[24][25][26] for direct alcohol fuel cells (DAFCs) and/or proton exchange membrane fuel cells (PEMFCs), that are regarded as promising future and clean power sources. 27,28 The addition of transition metal like nickel (Ni) to Pd can obviously further improve the overall electrocatalytic activities of Pd because of the bimetallic promotional effect.…”
Section: 2mentioning
confidence: 99%
“…However, upon heating in the MW at 100 °C, the duration of MW irradiation was a key to control the shape and size of the formed metal particles. Since noble nanometals such as Pd, Ag, and Au have been widely used as sensing materials, catalysts, and non-toxic drug carriers due to their unique properties [41][42][43][44], these synthesized metal nanoparticles could find potential applications in numerous areas of sensing, catalytic processes, and clinical applications.…”
Section: Discussionmentioning
confidence: 99%